2014
DOI: 10.1248/bpb.b13-00734
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Inhibits Fluphenazine-Induced Up-Regulation of <i>CDR1</i> in <i>Candida albicans</i>

Abstract: Over-expression of the Candida drug resistance gene CDR1 is a common mechanism generating azoleresistant Candida albicans in clinical isolates. CDR1 is transcriptionally activated through the binding of the transcription factor Tac1p to the cis-acting drug-responsive element (DRE) in its promoter. We previously demonstrated that the combination of fluconazole (FLC) and berberine (BBR) produced significant synergy when used against FLC-resistant C. albicans in vitro. In this study, we found that BBR inhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Previous studies reported that Eucalyptal D (Xu et al, 2019) geraniol (Singh and Sharma, 2018) and magnolol (Sun L. M. et al, 2015) which are substrates for Cdr1p efflux pumps, exert synergistic effects by simultaneously upregulating CDR1 and CDR2 expression, while competitively inhibiting FLC efflux. Numerous studies suggest that synergy results from increased intracellular drug accumulation caused by downregulated efflux pump genes in FLC-resistant strains (Garcia-Gomes et al, 2012;Zhu et al, 2014;Shao et al, 2016). Although Rh6G efflux gradually increased in all groups, much lower Rh6G efflux and CDR1 expression were detected in the BBH + FLC group, confirming previous results.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies reported that Eucalyptal D (Xu et al, 2019) geraniol (Singh and Sharma, 2018) and magnolol (Sun L. M. et al, 2015) which are substrates for Cdr1p efflux pumps, exert synergistic effects by simultaneously upregulating CDR1 and CDR2 expression, while competitively inhibiting FLC efflux. Numerous studies suggest that synergy results from increased intracellular drug accumulation caused by downregulated efflux pump genes in FLC-resistant strains (Garcia-Gomes et al, 2012;Zhu et al, 2014;Shao et al, 2016). Although Rh6G efflux gradually increased in all groups, much lower Rh6G efflux and CDR1 expression were detected in the BBH + FLC group, confirming previous results.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies revealed that ergosterol synthesis inhibition and apoptosis induced by endogenous ROS augmentation contribute to the synergistic effect of berberine plus FLC against C. albicans ( Xu et al, 2009 ; Xu et al, 2017 ; Yang et al, 2018 ). Furthermore, this combination could also downregulate efflux pump genes CDR1 and CDR2 overexpression ( Zhu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an important constituent of many herbs of Berberidaceae family such as Berberis vulgaris , berberine exerts its antifungal action by induction of mitochondrial dysfunction and increased ROS generation, and its effects are in synergy with fluconazole, even in fluconazole-resistant clinical isolates [ 54 56 ]. Moreover, berberine treatment could also culminate in disruption of cell wall integrity in C. albicans [ 57 ] and inhibit the overexpression of drug resistance gene CDR1 induced by fluphenazine [ 58 ]. Although berberine could induce apoptosis in many human cells such as HL-60 leukemia cells and thyroid carcinoma cells [ 59 , 60 ], berberine could recover the mitochondrial function induced by high-fat feeding in a rat model and could decrease the triglyceride accumulation in the liver in mice [ 61 , 62 ].…”
Section: Compounds Targeting Mitochondriamentioning
confidence: 99%
“…Berberine, an isoquinoline alkaloid, has been used for traditional medical systems in eastern countries. It possesses several biological activities including anti-inflammatory (Chu et al, 2014), anticancer (Yip and Ho, 2013;Cai et al, 2014), anti-diabetic (Rajendran et al, 2014), antibacterial (Wojtyczka et al, 2014), and antifungal functions (Zhu et al, 2014). The antioxidant capacity of berberine has demonstrated both direct (Jang et al, 2009;Bashir and Gilani, 2011) and indirect activities (Hwang et al, 2002;Tan et al, 2007).…”
Section: Antioxidant Effect Of Berberine and Its Phenolic Derivativesmentioning
confidence: 99%